2009
DOI: 10.1017/s0265051708008280
|View full text |Cite
|
Sign up to set email alerts
|

A tutor in your back pocket: reflections on the use of iPods and podcasting in an undergraduate popular music programme

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0265051708008280 How to cite this article: Steve Cooper, Crispin Dale and Steve Spencer (2009). A tutor in your back pocket: reections on the use of iPods and podcasting in an undergraduate popular music programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…These podcast materials were previously identified as an effective means of supporting student learning. (Cooper et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…These podcast materials were previously identified as an effective means of supporting student learning. (Cooper et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In a review of podcasting applications, Dale (2007) highlighted a number of potential benefits including the ability to meet a range of learning styles and developed key skills such as critical thinking and reflection. Similarly, Cooper et al (2009) discussed the role of podcasting in encouraging mobility of the learning experience, whereas Abt & Barry (2007) explored its benefits compared with written modes of communication. In her study of English language teacher training, Thompson (2007) refers to podcasting as the ultimate learning experience and authentic assessment.…”
Section: Introductionmentioning
confidence: 99%
“…3 In an undergraduate popular music program in England that used podcasts for delivering material, students reported that the podcasts motivated learners, enabled student interaction, offered time-shifted learning engagement, and personalized learning. 4 Educators can make use of podcasts in various ways. Teachers can engage in personal professional development by listening to podcasts, such as TED Talks (www.ted.com).…”
Section: Podcasts In Music Educationmentioning
confidence: 99%